ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI PERHIASAN LOGAM MULIA DI KOTA DENPASAR - Wulandari, I Gst Ayu Athina; Setiawina, Nyoman Djinar; Djayastra, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
Bali is a region which is known by it`s own gold and silver jewellery industries. It is scattered in all regency included Denpasar city. Based on times series data, the production growth are decrease.The main purpose of this study is to  analyse the affecting factors of production of it. The data has been used in this study is primary data. The technique analysis are descriptive analysis and MRA. The result shows that coefficient determination is 99,99 percent which means the variables can explaned about 99,99 percent, while remaining is 0,01 percent explaned by the variables outside the model, such as technology (casting), marketing, and government regulation about industry of handycraft. Material and labor have a positive and significant effect on production, but not for capital. Customers order as a moderating variabel for raw material and labor effect on production. It is  not  a moderating variabel for capital effect on production.
Keywords: industries, gold and silver jewellery, raw material, capital, labor, customers